2017
DOI: 10.1016/j.polymer.2017.11.038
|View full text |Cite
|
Sign up to set email alerts
|

From elastomers to thermoplasts – Precise control of isotactic propylene structure and properties and the role of different structural elements in its mechanical behaviour

Abstract: Studies of polypropylene with different degrees of isotacticity have shown a way of the rational design of material with predetermined mechanical properties starting from the synthesis stage already-controlled introducement of stereodefects will allow the smooth adjustment of the Young's modulus and elasticity in the range from plastic to elastomer materials. It was also revealed that modern theoretical models of the elasticity can be successfully applied not only for the description of the mechanical behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…(quenching) of polypropylene thin films [40]. A comparative analysis of the obtained results showed that only mesophase is observed at a fiber diameter of up to 8-9 μm.…”
Section: Structural Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…(quenching) of polypropylene thin films [40]. A comparative analysis of the obtained results showed that only mesophase is observed at a fiber diameter of up to 8-9 μm.…”
Section: Structural Analysismentioning
confidence: 92%
“…The X-ray patterns for composites are presented in Figure 5a and for nonwovens are shown in Figure 5b. According to X-ray data, the initial polypropylene and composites based on it are characterized by the presence of the reflections (110) at 14.1 • , (040) at 16.9 • , (130) at 18.5 • , (111) at 21.2 • , (131) + (041) at 21.9 • , (060) at 25.3 • , and (220) at 28.4 • , corresponding to a stable α-form with a monoclinic crystal lattice [9,40]. Reflections corresponding to the βor γ-form (e.g., (300) and (117), respectively) are not observed.…”
Section: Structural Analysismentioning
confidence: 99%
“…proved that the Young's modulus is linearly dependent on the sum of the crystalline phase content in a large set of polyethylene (PE) experiments. Shcherbina et al . obtained the dependence of the Young's modulus on crystallinity by calculating the macroscopic density of an isotactic polypropylene (iPP) sample.…”
Section: Introductionmentioning
confidence: 99%
“…The dependency of mechanical properties of PP on the DoC and cooling rate was studied in refs. . These data, compared together in ref.…”
Section: Introductionmentioning
confidence: 82%